2017
DOI: 10.18203/2349-3291.ijcp20172512
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and predictors of outcome in children admitted to PICU with acute encephalitis syndrome

Abstract: Background: Acute encephalitis syndrome (AES) is defined as the acute onset of fever and change in mental status (including symptoms such as confusion, disorientation, coma or inability to talk) and/or new onset seizures (excluding febrile seizures) in a person of any age at any time of the year. AES is reported mainly from Assam, Bihar, Tamil Nadu, Karnataka, Uttar Pradesh contributing approximately to 80% cases with case fatality rate of 20-25%. In view of paucity of clinical studies from Tamil Nadu, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…We found hyponatraemia (Na < 130 mEq/L) was significantly associated with mortality and morbidity. Similar result was also found by Sambasivam et al (9) They showed significant mortality (23.3%) with hyponatraemia.…”
Section: Discussionsupporting
confidence: 90%
“…We found hyponatraemia (Na < 130 mEq/L) was significantly associated with mortality and morbidity. Similar result was also found by Sambasivam et al (9) They showed significant mortality (23.3%) with hyponatraemia.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the mortality rate of patients with intracranial infections in children at our tertiary referral hospital was 25%. This mortality rate is smaller than the mortality rate from acute encephalopathy reported in India (36.67%) [ 5 ] and the mortality rate from bacterial meningitis reported in Mexico in 2003 (33%) [ 12 ]. The mortality rate in our study was not much different from a previous study in the same setting, Dr. Sardjito General Hospital in 2014 which amounted to 22.1% [ 13 ].…”
Section: Discussionmentioning
confidence: 66%
“…Several studies have been done specifically related to intracranial infection, encephalitis, meningitis, brain abscess or other intracranial infections. Research on factors associated with mortality in encephalitis has been done before and one study stated that the factors influencing mortality in pediatric patients with acute encephalitis who were admitted to the pediatric intensive care unit (PICU) were hyponatremia and patients who were in shock and received inotropes on admission [ 5 ]. Research conducted in adult patient subjects found that death in encephalitis was associated with cerebral edema, epileptic state and thrombocytopenia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The least number of cases that is, in the age group of 1month to less than 1 year constituted 9.26% of the total cases. This finding closely resembles the finding of Kakoti et al (2.98%) 5.…”
mentioning
confidence: 98%